OUR EXPERIENCE OF TREATMENT OF PANCREATIC CYSTS - V. A. Beloborodov; D. V. Sobotovitch; S. A. Kolmakov (Acta Biomedica Scientifica, 2012)
The aim. of the study was to determine the rational method, of surgical treatment of chronic pancreatic pseudocysts. The analysis of treatment of 82 patients with, chronic pancreatic pseudocysts cysts is presented, in the article. 68 patients had. punctures and drainage. On the basis of performed research, we found, out that chronic pancreatic pseudocysts of any size and. location developed, on the background, of pancreatitis in the absence of signs of sequestration, were an indication, for puncture and. drainage under ultrasound, guidance. The absence of recovery effect of mini-invasive treatment causes reasonable indications for open surgery.